Mechanisms and effects of aspirin to cancer cells - Wan, Yiguo (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Aspirin, everyone knows it is an anti-inflammatory drug, has great promise mostly for the prevention and treatment of cancer by using a number of methodologies. Its anti-cancer property come from its induction of apoptosis, inhibition of cell growth, and disruption of important signaling pathways. By exploring the mechanisms through which aspirin affects cancer cells, particularly having the impact on signaling pathways like non-coding RNAs (ncRNAs), and controlling the activity of platelets. It is also mentioned that the inhibition of cyclooxygenase (COX) enzymes is involved in aspirin’s primary action, leading to lower rate of inflammatory mediators produced and changing cellular signaling networks. The modulation of ncRNAs, especially in connection to specific cancer pathways, concentrating its role in cancer treatment for many areas. However, although huge potential of the drug exhibits, the use of aspirin is not without risks. Common symptoms such as gastrointestinal discomfort and bleeding are in considering. As all mentioned below, numerous good results in improved treatment approaches for patients will come out, follow the continued investigation into the many ways that aspirin affects cancer cells.